Post-transplantation cyclophosphamide reduces the incidence of acute graft-versus-host disease in patients with acute myeloid leukemia/myelodysplastic syndromes who receive immune checkpoint inhibitors after allogeneic hematopoietic stem cell transplantation. Issue 2 (26th February 2021) - Saberian, Chantal; Abdel-Wahab, Noha; Abudayyeh, Ala; Rafei, Hind; Joseph, Jacinth; Rondon, Gabriela; Whited, Laura; Gruschkus, Stephen; Fa'ak, Faisal; Daher, May; Knape, Cristina; Safa, Houssein; et al.
Abstract : Background: Immune checkpoint inhibitors (ICIs) are being used after allogeneic hematopoietic stem cell transplantation (alloHCT) to reverse immune dysfunction. However, a major concern for the use of ICIs after alloHCT is the increased risk of graft-versus-host disease (GVHD). We analyzed the association between GVHD prophylaxis and frequency of GVHD in patients who had received ICI therapy after alloHCT. Methods: A retrospective study was performed in 21 patients with acute myeloid leukemia (n=16) or myelodysplastic syndromes (n=5) who were treated with antiprogrammed cell death protein 1 (16 patients) or anticytotoxic T lymphocyte-associated antigen 4 (5 patients) therapy for disease relapse after alloHCT. Associations between the type of GVHD prophylaxis and incidence of GVHD were analyzed. Results: Four patients (19%) developed acute GVHD. The incidence of acute GVHD was associated only with the type of post-transplantation GVHD prophylaxis; none of the other variables included (stem cell source, donor type, age at alloHCT, conditioning regimen and prior history of GVHD) were associated with the frequency of acute GVHD. Twelve patients received post-transplantation cyclophosphamide (PTCy) for GVHD prophylaxis. Patients who received PTCy had a significantly shorter median time to initiation of ICI therapy after alloHCT compared with patients who did not receive PTCy (median 5.1 months compared with 26.6 months). Despite early ICI therapy initiation, patients who received PTCy had a lower observed cumulative incidence of grades 2–4 acute GVHD compared with patients who did not receive PTCy (16% compared with 22%; p=0.7). After controlling for comorbidities and time from alloHCT to ICI therapy initiation, the analysis showed that PTCy was associated with a 90% reduced risk of acute GVHD (HR 0.1, 95% CI 0.02 to 0.6, p=0.01). Conclusions: ICI therapy for relapsed acute myeloid leukemia/myelodysplastic syndromes after alloHCT may be a safe and feasible option. PTCy appears to decrease the incidence of acute GVHD in this cohort of patients.